State and the Commodification of Natural Resources: A Framework of Analysis - Osawe, Anthony Ikhide (African Journal of Stability and Development (AJSD), 2022)
The commodification of nature and framing of the environment as natural resources have become increasingly prominent in international environmental governance discuss because most natural resources are traded through organised commodity exchanges. The result the depletion of natural resources with the attendant negative impact on the environment and the poor. Commodification has brought about the framing of the environment as a ‘natural resource’ and has become increasingly prominent in international environmental governance. The role of international organisations like the World Bank, United Nations Environmental Programme (UNEP) through Payments for Ecosystem Services (PES) and The Economics of Ecosystems and Biodiversity (TEEB) and its adoption by the Convention on Biological Conservation are indications of the concepts wide-ranging appeal. This paper sees commodification and the role of different actors as putting a price on nature’s goods in the form of species banking and conservation finance as a strategy for solving a range of environmental problems from climate change to deforestation. The paper concluded that commodification should be seen as an approach to bringing ethics into natural resources management, capable of generating incentives that are required to guide people towards ethical use of natural resources to the advantage of all.